Interference of metal ions on the bioluminescent signal of firefly, Renilla, and NanoLuc luciferases in high-throughput screening assays - Canyelles i Font, Francesca; Żukowski, Krzysztof; Khan, Masroor A.; Kwiatek, Dorota; Kolanowski, Jacek L. (Frontiers in Chemistry, 2024)
Bioluminescent high-throughput screening (HTS) assays, based largely on the activity of firefly (FLuc), Renilla (RLuc), and/or NanoLuc (NLuc) luciferases, are widely utilised in research and drug discovery. In this study, we quantify the luciferase-based real-life HTS assay interference from biologically and environmentally relevant metal ions ubiquitously present in buffers, environmental and biological matrices, and as contaminants in plastics and compound libraries. We also provide insights into the cross-effects of metal ions and other key experimental and biological reagents (e.g., buffer types, EDTA, and glutathione) to inform HTS assay design, validation, and data interpretation. A total of 21 ions were screened in three robust HTS assays (“SC” assays) based on the luminescence of FLuc, RLuc, and NLuc luciferases. Three newly optimised HEPES buffer variants (“H” assays) were developed for direct luciferase comparison. Interference in bioluminescent signal generation was quantified by calculating the IC50 values from concentration-dependent experiments for selected highly active and relevant metal ions. Metal ion inhibition mechanisms were probed by variations in specific reagents, EDTA, GSH, and the sequence of addition and buffer composition. In this study, we revealed a significant impact of metal ions’ salts on luciferase-mediated bioluminescence, even at biologically and environmentally relevant concentrations. The extent of signal interference largely aligned with the Irving–Williams series of metal ion–ligand affinities (Cu > Zn > Fe > Mn > Ca > Mg), supporting previous reports on metal ion-dependent FLuc inhibition. However, the absolute magnitude and relative extent of signal reduction by metal ions’ salts differed between SC and H assays and between luciferases, suggesting a complex network of metal ions’ interactions with enzymes, substrates, reactants, and buffer elements. The diversity of the tested conditions and variability of responses provided insights into potential interference mechanisms and synergies that may exacerbate or alleviate interference. The beneficial influence of EDTA and the impact of glutathione, present natively in cells, on bioluminescence readout were pinpointed. Given the ubiquity of metal ions in analysed samples, the causative role in false-positive generation in drug discovery, and the wide breadth of luciferase-based assays used in screening, awareness and quantification of metal influence are crucial for developing assay validation protocols and ensuring reliable screening data, ultimately increasing the critical robustness of bioluminescence-based HTS assays.